Efficiency of Zakat Collection and Distribution by the National Zakat Agency (Baznas) in Regencies/Cities in Indonesia - Isti Khoirul Rochmah; Muhammad Sholahuddin; Imronudin Imronudin (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the efficiency of zakat collection and distribution by the National Zakat Agency (Baznas) in districts/cities in Indonesia. This study uses a descriptive quantitative approach. The population in this study is all companies listed on the Indonesia Stock Exchange in 2019-2021. The sampling technique used in this study is non-probability sampling, specifically purposive sampling. The data sources for this study are audited financial reports issued by each National Zakat Management Agency (BAZNAS) in districts/cities on the Digital Zakat Information System or the official Digital Service Interface of BAZNAS RI. The data collection method used in this study was documentary research (literature review). The data analysis method used in this study was Data Envelopment Analysis (DEA), a non-parametric technique used to assess the technical efficiency of decision-making units (DMUs). The results of this study indicate that technical efficiency in zakat management does not solely depend on the size of input allocation but is more determined by managerial effectiveness in managing inputs to produce optimal outputs. The combined approach of DEA and FDH has proven capable of providing a more comprehensive understanding of the institutional performance of BAZNAS. Therefore, this study supports the importance of developing a data-based evaluation system and structured institutional development strategies focused on long-term efficiency, particularly in zakat management as a public trust and an instrument of social justice at the local level